Land rights, rental markets and the post-socialist cityscape - Paul Casta\~neda Dower; William Pyle (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
Inefficiently organized, factory-dominated cityscapes have been one of the more enduring legacies of the twentieth century experiment with socialist central planning in Eastern Europe and the Soviet Union. Drawing on a unique survey of large, formerly state-owned urban industrial firms in Russia, we explore how land tenure reforms affect the pace at which this legacy is being erased. Specifically, the privatization of plots is shown to promote the development of a rental market that transfers land use rights away from socialist-era industrial users. We address the potential endogeneity of land tenure in two ways, including using a measure of regional variation in urban land policy as an instrumental variable.
URN:NBN:fi:bof-201611211485
Keywords: D22; D23; O18; P25; P26; R14; 330